Identification of Best Practices of Higher Education Leadership in Shaping Student Character following Islamic Guidance - Rini Fitria; Abdul Rosid; Suwarni; Amirul Syah; Musyarrafah Sulaiman Kurdi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The study aimed to highlight best practices that showcased effective higher education leadership in character development at the university, substantiating these practices with compelling evidence rooted in Islamic principles. In pursuing this objective, a mixed-method approach was employed in the past. Qualitative data was collected through interviews and document analysis, while surveys and questionnaires provided quantitative insights. The study also reviewed relevant literature to contextualize Fatmawati University's character development efforts. The findings from this past study were illuminating. Fatmawati University effectively integrated Islamic ethics and morality into its academic curriculum through courses like